STRUCTURAL-FUNCTIONAL APPROACH IN THE WORLD-THEORETICAL KNOWLEDGE OF TERRITORIAL COMMUNITIES - Christopher Daniel Colell; O. V. Kneysler; N. Ya. Spasiv; І. М. Fedorovych (Фінансово-кредитна діяльність: проблеми теорії та практики, 2019)
Taking into account the limited theoretical study of the territorial communities, the aspects of their scientific knowledge from the standpoint of the structural-functional approach are highlighted. Using the structural-functional approach, the functions of territorial communities as the subjects of local self-government are disclosed, their division into public and private functions is substantiated. It has been established that the functional research of the territorial communities is the most successful way to reveal their economic content and essence. It has been determined that the theory of the territorial communities’ functions originates from the legislation of Ukraine, is based on the experience of local self-government bodies and the achievement of scientific thought in the field of local self-government. At the same time, a critical review of the theoretical approaches of modern scholars to the classification of the territorial communities’ functions allowed to state not the objectivity of these approaches, but the fields of scientific interests of each of them. The territorial community, performing public and private functions, ensures the realization of the basic social and economic rights of its members, involving them to local self-government. The criteria for this classification are the objective nature of the complex of tasks that local self-government and the territorial communities try to solve as their primary subjects. The variety and diversity nature of the tasks, arising before local government, produces the directions of the activities of the territorial communities, namely their functions. This process is interdependent and dynamic, since the range of functions is wide and permanently variable.